Tanggung Jawab Kurator Atas Berkurangnya Nilai Harta Pailit (Boedel Pailit) Debitur Berdasarkan Undang – Undang No.37 Tahun 2004 Tentang Kepalitan Dan Penundaan Kewajiban Pembayaran Utang - Eli, Eli Ristiana Simandalahi; Habeahan, Besty (Lembaga Dongan Dosen, 2025)
This study discusses the responsibility of the curator for the reduction of the value of the debtor's bankruptcy assets (bankruptcy boedel) which is reviewed based on Law No. 37 of 2004 concerning Bankruptcy and PKPU. The formulation of the problems raised includes how the curator's responsibility in carrying out the management of bankruptcy assets where the value of the bankruptcy assets is reduced and the factors that cause the reduction of bankruptcy assets. The results of the study discuss the responsibility of curators who are very important in managing and settling bankruptcy assets and have two forms of responsibility for bankruptcy assets, namely personal responsibility and also responsibility in their professional capacity as curators. And if it is known that the curator committed fraud in the process of managing bankruptcy assets, the party who feels aggrieved can be prosecuted civilly and criminally if it meets the elements of unlawful acts.